Managing the surge in demand for blood following mass casualty events: Early automatic restocking may preserve red cell supply. Issue 1 (July 2016) - Glasgow, Simon; Vasilakis, Christos; Perkins, Zane; Brundage, Susan; Tai, Nigel; Brohi, Karim
Abstract : BACKGROUND: Traumatic hemorrhage is a leading preventable cause of mortality following mass casualty events (MCEs). Improving outcomes requires adequate in-hospital provision of high-volume red blood cell (RBC) transfusions. This study investigated strategies for optimizing RBC provision to casualties in MCEs using simulation modeling. METHODS: A computerized simulation model of a UK major trauma center (TC) transfusion system was developed. The model used input data from past MCEs and civilian and military trauma registries. We simulated the effect of varying on-shelf RBC stock hold and the timing of externally restocking RBC supplies on TC treatment capacity across increasing loads of priority one (P1) and two (P2) casualties from an event. RESULTS: Thirty-five thousand simulations were performed. A casualty load of 20 P1s and P2s under standard TC RBC stock conditions left 35% (95% confidence interval, 32–38%) of P1s and 7% (4–10%) of P2s inadequately treated for hemorrhage. Additionally, exhaustion of type O emergency RBC stocks (a surrogate for reaching surge capacity) occurred in a median of 10 hours (IQR, 5 to >12 hours). Doubling casualty load increased this to 60% (57–63%) and 30% (26–34%), respectively, with capacity reached in 2 hours (1–3 hours). The model identified a minimum requirement of 12 U of on-shelf RBCs per P1/P2 casualty received to prevent surge capacity being reached. Restocking supplies in an MCE versus greater permanent on-shelf RBC stock holds was considered at increasing hourly intervals. T -test analysis showed no difference between stock hold versus supply restocking with regard to overall outcomes for MCEs up to 80 P1s and P2s in size ( p < 0.05), provided the restock occurred within 6 hours. CONCLUSION: Even limited-sized MCEs threaten to overwhelm TC transfusion systems. An early-automated push approach to restocking RBCs initiated by central suppliers can produce equivocal outcomes compared with holding excess stock permanently at TCs. LEVEL OF EVIDENCE: Therapeutic/care management study, level IV. Abstract : Supplemental digital content is available in the text.